2016
DOI: 10.1017/s0029665116000239
|View full text |Cite
|
Sign up to set email alerts
|

Meal irregularity and cardiometabolic consequences: results from observational and intervention studies

Abstract: Studying irregular meal patterns fits in with the latest research focusing not only on what people eat but also when they eat, also called chrono-nutrition. Chrono-nutrition involves studying the impact of nutrition on metabolism via circadian patterns, including three aspects of time: (ir)regularity, frequency and clock time. The present paper aimed to narratively review research on irregular meal patterns and cardiometabolic consequences. Only few cross-sectional studies and prospective cohort studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 78 publications
0
67
1
3
Order By: Relevance
“…Chrono-nutrition is an emerging field of research that refers to the temporal variations in the patterning and distribution of food and beverage intake or eating occasions (EOs), including meals and snacks, across the day (1). Animal studies have shown that deviations from habitual eating patterns negatively affect metabolic and physiologic functions that are also regulated by circadian clock systems in the suprachiasmatic nuclei and peripheral tissues (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Chrono-nutrition is an emerging field of research that refers to the temporal variations in the patterning and distribution of food and beverage intake or eating occasions (EOs), including meals and snacks, across the day (1). Animal studies have shown that deviations from habitual eating patterns negatively affect metabolic and physiologic functions that are also regulated by circadian clock systems in the suprachiasmatic nuclei and peripheral tissues (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The group of DSPD patients and the control group were similar in terms of age, height, smoking status, and alcohol consumption. 1 BMI was calculated using self-reported height and weight. 2 DHD-index score has a minimum of 0 and a maximum of 90.…”
Section: Characteristics Of Study Populationmentioning
confidence: 99%
“…There is an increasing interest, besides what people eat, in when they eat [1]. The relationship between dietary intake and the circadian clock is called chrono-nutrition, which indicates the impact of the timing of eating on health [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional activators brain and muscle Arnt-like protein-1 (BMAL1) and circadian locomotor output cycles kaput (CLOCK) induce expression of their own repressors cryptochrome (CRY) and period (PER), resulting in generating 24 hours oscillations. Several human studies revealed correlation between irregular eating times and the risk of obesity and insulin resistance [1,2], and restriction of feeding time contributes to prevent and ameliorate these diseases [3,4]. Thus, feeding time is important to maintaining for human health.…”
Section: Introductionmentioning
confidence: 99%